Empowering radiation therapists: The role of an African Community of Practice in developing radiation Therapist education curriculum - Yat Tsang; Kofi Adesi Kyei; Sandra Ndarukwa; Katie Wakeham; Abiola Fatimilehin; Kimyakhanim Bakhinshova; Lisbeth Cordero Mendez (Technical Innovations & Patient Support in Radiation Oncology, 2024)
Objectives: Supported by the International Atomic Energy Agency (IAEA), the African Regional Cooperative Agreement for Research, Development and Training (AFRA) invited African Member States (MS) with a radiation therapy facility to engage in a 3-day workshop to develop a robust road map for educational standards in radiation therapist (RTT) training. The aim of the paper was to make recommendations of how the African MS could drive forward high educational standards in RTT training and education in Africa. Methods: A pre-workshop survey was developed and sent to the participants to gather background information on each MS’s national RTT training standards. An online survey was sent to all African MS with a radiation therapy facility. Two international RTT education-training experts were tasked by the IAEA to support and facilitate the workshop, which consisted of presentations and discussions around the current RTT training schemes in African MS and aspects of modern training methodology. The agenda of the workshop was structured with the aim to simulate discussions on RTT education and training standards among participants from African MS. Results: Sixteen African MS completed the pre-workshop survey. The median number of radiotherapy centres within a MS was 3 (range 1––15). All MS provided two-dimensional radiation therapy services as a minimum while 75 % (12/16) MS could offer three-dimensional conformal radiation therapy service. Thirty-eight percent (6/16) reported that they had no radiation therapy machine service maintenance contracts with vendors and 56 % (9/16) MS had no biomedical engineers on site for unplanned and planned machine maintenance. The median number of RTTs at national level among MS was 23 (range 7–73). Fifty-six percent (9/16) MS had a RTT specific national training programme with 75 % (12/16) MS having clinical attachments for 6 months or more. Representatives from 12 African MS attended the AFRA workshop. An African Community of Practice (CoP) in developing Education Curriculum for RTT was established as an outcome of the workshop with the aim to facilitate knowledge exchange and drive quality initiatives among participating African MS. Four work streams were proposed to form the CoP: RTT academic qualifications, core competencies in RTT education and training, RTT education faculty composition and peer review process in RTT education curricula among African MS. Conclusion: By fostering collaboration, sharing knowledge, and advocating for improved policies, the African COP in developing Education Curriculum for RTT can make significant strides toward developing a RTT education curriculum that not only meets the unique challenges of the African continent but also aligns with global standards.